Detection of Intracranial Hemorrhage with Susceptibility-Weighted MR Sequences - Liang, Luxia (AJNR Am J Neuroradiol, 1999)
BACKGROUND AND PURPOSE: Detection of hemorrhage is important in the diagnosis and management of a variety of intracranial diseases. We evaluated the sensitivity of the following sequences for depicting chronic hemorrhagic foci associated with susceptibility dephasing: gradient-recalled echo (GRE) imaging, GRE-type single-shot echo-planar imaging (GRE-EPI), spin-echo–type single-shot echo-planar imaging (SE-EPI), turbo spin-echo (TSE) imaging, half-Fourier single-shot turbo spin-echo (HASTE) imaging, and segmented HASTE (s-HASTE) imaging. To our knowledge, no previous comparison has been made with these techniques in the same patient. METHODS: Fifty patients with suspected chronic hemorrhage were examined prospectively with the above six sequences. Contrast-to-noise ratio (CNR), sensitivity to detection of lesions, conspicuity of internal architecture, and sensitivity to small hemorrhagic foci were evaluated. RESULTS: Hemorrhagic foci were found in 35 patients. The CNR of the GRE, GRE-EPI, SE-EPI, TSE, s-HASTE, and HASTE sequences was 30.9, 23.7, 3.6, 6.1, −29.3, and −13.1, respectively; the number of small hemorrhagic foci detected was 85, 96, 44, 22, two, and one, respectively, for the supratentorial white matter; 70, 40, 19, four, zero, and zero, respectively, for the supratentorial cortical/subcortical region; and 73, 50, 26, 37, zero, and zero, respectively, for the infratentorial/skull-base region. CONCLUSION: The GRE sequence was best for detecting susceptibility dephasing associated with chronic intracranial hemorrhage. GRE-EPI, while comparable to GRE in the supratentorial compartment, was reduced in its sensitivity near the skull base, and may be used as an alternative to GRE in uncooperative, unsedated, pediatric, or claustrophobic patients. SE-EPI should not be used in screening for intracranial hemorrhage.